Antimicrobial drug resistance pattern of uropathogens isolated from patients with urinary tract infection at Chitwan Medical College (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Urinary tract infections (UTIs) represent one of the most frequently occurring bacterial infections in all age ranges, with their incidence rising significantly in the elderly. Antibiotic resistance in recent years has become a major threat to public health globally. This study aimed to identify the antimicrobial drug resistance pattern of uropathogens isolated from patients with UTI.Material and Methods: A descriptive cross-sectional study was conducted to assess antimicrobial drug resistance pattern of uropathogens isolated from patients with UTI at chitwan medical college, from 15st January 2025 to 15th April 2025. A total of 140 reports with culture positive sample with UTI that came to microbiology lab during the study period and those fulfilling the inclusion criteria was included in the study. Data regarding patient information, bacterial isolates, their susceptibility to various antibiotics and other information were collected, compiled, entered and analyzed. The results are presented in frequency and percentage.Results: Among the identified pathogens, Escherichia coli was the most frequently isolated organism. The highest resistance among these isolates was observed against Nalidixic acid (70.3%) followed by Ampicillin (67.3%), Cefalotin (63.4%) and Ticarcillin (61.4%). UTI was found to be more prevalent in the female gender and majority of the patients were from 61-75 years.Conclusion: E. coli was the most commonly isolated organism. Urinary pathogenesis showed resistance to commonly used antibiotics.